VscF in T3SS1 Helps to Translocate VPA0226 in Vibrio parahaemolyticus - Lian, Lele; Xue, Jiao; Li, Wanjun; Ren, Jianluan; Tang, Fang; Liu, Yongjie; Xue, Feng; Dai, Jianjun (Frontiers in Cellular and Infection Microbiology, 2021)
In Vibrio parahaemolyticus, type III secretion system 1 (T3SS1) is a major virulence factor that delivers effectors into the host eukaryotic cytoplasm; however, studies on its infection mechanism are currently limited. Here, to determine the function of the vscF gene, we constructed the vscF deletion mutant ΔvscF and complementation strain CΔvscF. Compared with those of wild-type POR-1 and CΔvscF, the cytotoxic, adherent, and apoptotic abilities of ΔvscF in HeLa cells significantly reduced (P <0.01). Further, in infected HeLa cells, the mutant strain reduced the translocation rates of VP1683 and VP1686 effectors compared with the wild-type and complementation strains. BLAST search showed that vscF is homologous to the MixH needle protein of Shigella flexneri, indicating that the vscF gene encodes the needle protein of T3SS1 in V. parahaemolyticus. Additional translocation assays showed that VPA0226 translocated into the HeLa eukaryotic cytoplasm via T3SS1, indicating that VPA0226 belongs to the unpublished class of T3SS1 effectors. In conclusion, our data indicate an essential role of vscF in V. parahaemolyticus T3SS1 and reveal that VPA0226 is secreted into the host cell cytoplasm via T3SS1. This study provides insights into a previously unexplored aspect of T3SS1, which is expected to contribute to the understanding of its infection mechanism.